How mothers make their choice : comparative perspectives between working mothers and housewives in Singapore. - Ngui, Michelle. (2012)
With an increasing number of graduate mothers in Singapore, greater emphasis is placed on the dual role that graduate mothers play. The Singapore government has formulated family-friendly policies and improved infrastructure to help mothers balance their work and family commitments better. However, the percentage of working women is still lower as compared to many developed countries. Many argue that this is due to women in Singapore who suffer from the gender ideology of the state, where domestic chores and childcare are still largely regarded as the responsibility of the women is paradoxical to their expectations of working mothers. Majority of literature in this aspect tend to focus on state policies, or the perspectives of working women but little research has been done on other deciding factors and housewives. This paper thus aims to examine the gender ideology and factors that are define mothers’ choices to work or stay home. In-depth interviews with 10 working mothers and 10 housewives were conducted in this research.